Efeitos da musicoterapia improvisacional no tratamento de crianças com Transtorno do Espectro do Autismo - Marina Horta Freire (2014)
BACKGROUND: The Autism Spectrum Disorder (ASD) is a neurodevelopmental disturb that affects social communication and behaviors since first childhood. Music is related as a treatment for this population since the beginning of Music Therapy. However, controlled studies are scant. Researches that investigate ASD and music show Music Therapy as an eligible way for improving social and communicational abilities. This study aims to investigate the effects of Improvisational Music Therapy on the treatment of preschool children with ASD. METHODS: Forty five children aged between 2 and 6 years and diagnosed with ASD were assigned to two conditions: Control (n=19) and Intervention (n=26). They were submitted to evaluation before and after condition (T1 and T2). During interview, four scales were used in order to evaluate parents (BDI, LEES, PSI, WHOQOL) and six scales were used in order to evaluate children (CARS, ATEC, ICA, ABC, CGAS, CGI). Music Therapy scales (ENR1, ENR2, and IAPs) were measured by session observation. Intervention group received individual weekly sessions on Improvisational Music Therapy. Both group kept usual care during study. Intervention group participated of maintenance assessment 7 weeks after T2. Statistical analysis were made using SPSS 17.0 for Windows. RESULTS: Groups were paired on T1 and different on T2. On Intervention group, the differences between T1 and T2 were statistically significant for all scales and subscales. Control condition showed significance only on one subscale for speech, language and communication. Generally, Intervention group showed moderate to large effect size, while Control group showed small effect size. Maintenance assessment showed that some symptoms worsened after T2. The differences between T1 and T2 for parents assessments showed significant decrease of parental stress on both group, and significant decrease of depression only on Intervention Group (p<0.01). Parents depression, expressed emotion and parental stress were correlated to ASD severity. Scales witch evaluate specific symptoms of TEA were significantly correlated with Music Therapy scales. CONCLUSIONS: The results have shown that Improvisational Music Therapy can bring positive effects to children with ASD. Significant evidence supports the value of Music Therapy in promoting improvements on communication and socialization. Improvements are also observed on these childrens music development through Music Therapy Assessments. Results also suggest that childrens clinical improvements may help their parents depression and stress, but results are still inconclusive. Correlations between scales and internal consistency analysis suggest that these scales can be reliable tools for evaluating treatments and improvements in people with ASD.